Dispensationalism, Israel and the Church The Search for Definition - Blaising, Craig A.; Bock, Darrell L (Grand Rapids Zondervan Publishing House, 1992)
The relationship between Israel and the church is a crucial reference point in theology, especially in distinguishing between dispensational and nondispensational schools of thought. The writers of this book view Israel and the church as distinct theolo
Keywords: Dispensationalism. Bible. -- New Testament -- Relation to the Old Testament. Dispensationalism. Israel (Christian theology) Church. Bible. -- New Testament. Bibel -- Altes Testament Bibel -- Neues Testament Aufsatzsammlung Altes Testament. Neues Testament. Aufsatzsammlung